Childhood adversity and emerging psychotic experiences: a network perspective - Qiao, Zhiling; Lafit, Ginette; Lecei, Aleksandra; Achterhof, Robin; Kirtley, Olivia J; Hiekkaranta, Anu P; Hagemann, Noëmi; Hermans, Karlijn S F M; Boets, Bart; Reininghaus, Ulrich; Myin-Germeys, Inez; van Winkel, Ruud (Schizophrenia bulletin, 2024)
Childhood adversity is associated with a myriad of psychiatric symptoms, including psychotic experiences (PEs), and with multiple psychological processes that may all mediate these associations.Using a network approach, the present study examined the complex interactions between childhood adversity, PEs, other psychiatric symptoms, and multiple psychological mediators (ie, activity-related and social stress, negative affect, loneliness, threat anticipation, maladaptive cognitive emotion regulation, attachment insecurity) in a general population, adolescent sample (n = 865, age 12-20, 67% female).Centrality analyses revealed a pivotal role of depression, anxiety, negative affect, and loneliness within the network and a bridging role of threat anticipation between childhood adversity and maladaptive cognitive emotion regulation. By constructing shortest path networks, we found multiple existing paths between different categories of childhood adversity and PEs, with symptoms of general psychopathology (ie, anxiety, hostility, and somatization) as the main connective component. Sensitivity analyses confirmed the robustness and stability of the networks. Longitudinal analysis in a subsample with Wave 2 data (n = 161) further found that variables with higher centrality (ie, depression, negative affect, and loneliness) better predicted follow-up PEs.Pathways linking childhood adversity to PEs are complex, with multifaceted psychological and symptom-symptom interactions. They underscore the transdiagnostic, heterotypic nature of mental ill-health in young people experiencing PEs, in agreement with current clinical recommendations.
Online veröffentlicht: 15. Juni 2023
Gesehen am 26.02.2024